First men in the moon [videorecording (DVD)] - Hyer, Martha; Judd, Edward, 1932-2009; Jeffries, Lionel; Wells, H. G. (Herbert George), 1866-1946 (Columbia Tristar Home Video, 2002)
As a team of United Nations astronauts prepares for a moon mission, they are confused by a man who claims he, his fiancee and a scientist journeyed to the moon 65 years ago and were attacked by grotesque, human-like forms that live in immense crystal caverns.